Formulasi dan uji aktivitas salep ekstrak etanol daun kelor (Moringa oleifera L.) sebagai antibakteri Staphylococcus aureus metode Kirby bauer - Puspita, Eka; Dianita, Puspita; Kusuma, Tiara (Borobudur Pharmacy Review, 2023)
Infection is the highest disease in Indonesia caused by bacteria. One of the bacteria that can cause infection is Staphylococcus aureus which is a gram-positive bacterium. Moringa leaves contain antioxidants which are secondary metabolites of catechol tannins, triterpenoid tannins, flavonoids, anthraquinone saponins, alkaloids, and reducing sugars. The purpose of this study was to determine the antibacterial activity of moringa leaf ointment (Moringa oleifera L. ) as an antibacterial for Staphylococcus aureus. This research method uses experimental. The steps that have been carried out include extraction by maceration from the simplicia powder of Moringa leaves (Moringa oleifera L. ) with 96% ethanol then in a water bath until the extract is thick. Moringa leaf ointment (Moringa oleifera L. ) with a concentration of F1 5%, F2 10%, F315% has met the requirements for good physical properties tests including organoleptic test, homogeneity test, pH, adhesion, spreadability and viscosity. The agar medium used was Nutrient Agar (Na) with the Kirby-Bauer method (Disc Diffusion) divided into 5 groups namely base, positive control, negative control, F1, F2, F3. The results of data analysis in this study used SPSS Statistics version 25 which showed a value (p> 0.05) which could be interpreted as data that there was no difference in the inhibition zone affected by Moringa leaf ethanol extract ointment against Staphylococcus aureus bacteria . The best result of the three formulas is F3 15%.